2014
DOI: 10.1016/j.ijpp.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Dental development pathology in wild artiodactyls: Two prehistoric case studies from France

Abstract: In this paper we report two unique cases of dental development anomalies observed on prehistoric faunal material from France. The first is a severely malformed first incisor from a red deer, dated to the 13th-12th millennium BC, which is interpreted as a composite odontoma, a rare pseudo-tumor of odontogenic origin. The second is a Mesolithic (9th-8th millennium BC) wild boar skull presenting an anomalous tooth row including a duplication of the upper left second premolar. Both pathologies are discussed in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…We are also not aware of any previously published case of this type of tumor in the archeozoological literature. As has been stated recently (Binois et al, 2014), rare and unique pathological findings in prehistoric animals should always be reported, as they are of interest both for the archeozoologist who may encounter similar cases in his material as well as for the pathologist studying corresponding cases in recent animals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We are also not aware of any previously published case of this type of tumor in the archeozoological literature. As has been stated recently (Binois et al, 2014), rare and unique pathological findings in prehistoric animals should always be reported, as they are of interest both for the archeozoologist who may encounter similar cases in his material as well as for the pathologist studying corresponding cases in recent animals.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding odontogenic tumors and tumor-like lesions in prehistoric wild animals, thus far only a number of odontomas (tumor-like malformations or hamartomas; Praetorius and Piattelli, 2005a,b;Brown et al, 2007) in proboscideans (Van Essen, 2004) and a single case of odontoma in a red deer (Cervus elaphus) (Binois et al, 2014) have been reported. The present paper reports the case of an odontogenic tumor in a red deer from the Late Pleistocene of Rochedane, France.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the effects of artificial selection, inbreeding and general shortening of the skull. 4447 Dental abnormalities in animals are often the result of their domestication or captivity and they occur during the formation and development of a dental structure. 32…”
Section: Dental Abnormalitiesmentioning
confidence: 99%
“…Although every species has a given dental formula, individuals of the species can deviate from this generic formula. 47 The presence of supernumerary teeth (Figures 1 and 2), also referred to as hyperdontia or polyodontia, occurs in most species of vertebrates, including man. 46 Two types of polydontia have been described.…”
Section: Supernumerary Teethmentioning
confidence: 99%
See 1 more Smart Citation